Anstieg der Lohnungleichheit, Rückgang der Tarifbindung und~Polarisierung - Dirk Antonczyk; Bernd Fitzenberger; Katrin Sommerfeld (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– This article aims at describing and discussing the development of wage inequality in Germany in relation to the decline in collective wage bargaining, as this could be the institutional cause for the development since the 1990s. At the same time, the polarization hypothesis is discussed. Wage inequality has been strongly increasing over the entire wage distribution since the 1990s. The rise in wage dispersion between 2001 and 2006 can barely be explained by the strong decline in collective bargaining coverage. Instead, changing wage differentials across and within industries are the main explanation for the rise in wage inequality. This increasing wage flexibility is observed both among industries covered by collective bargaining and among those not covered. Polarization in employment in Germany can be explained by the decline in routine tasks. In contrast, there is no evidence of a polarization of wages in Germany since the 1990s.
Keywords: J31; J51; J52; C21; 330; Lohnunterschied - Entwicklung; Lohnentwicklung; Tarifbindung - Entwicklung; Lohnflexibilität; Einkommenseffekte; Lohnstruktur; technischer Wandel; Arbeitskräftenachfrage; Qualifikationsstruktur; sektorale Verteilung; Wirtschaftszweige; Westdeutschland; Bundesrepublik Deutschland